A multidimensional functional trait analysis of resource exploitation in European ants. Issue 10 (1st October 2015) - Retana, Javier; Arnan, Xavier; Cerdá, Xim
Abstract : The major factors explaining ecological variation in plants have been widely discussed over the last decade thanks to numerous studies that have examined the covariation that exists between pairs of traits. However, multivariate relationships among traits remain poorly characterized in animals. In this study, we aimed to identify the main multivariate trait dimensions that explain variance in important functional traits related to resource exploitation in ants. To this end, we created a large ant trait database. This database includes information on 11 traits that are important in ant resource exploitation; data were obtained for 150 European species found in different biomes. First, we examined the pairwise correlations between the traits included in the database. Second, we used multivariate analyses to identify potential trait dimensions. Our study shows that, to a great extent, resource exploitation strategies align along two main trait dimensions. The first dimension emerged in both the overall and group‐specific analyses, where it accounted for the same pairwise trait correlations. The second dimension was more variable, as species were grouped by levels of taxonomy, habitat, and climate. These two dimensions included most of the significant pairwise trait correlations, thus highlighting that complementarity, but also redundancy, exists among different pairs of traits. The first dimension was associated with behavioral dominance: dominance was associated with large colony size, presence of multiple nests per colony, worker polymorphism, and a collective foraging strategy. The second dimension was associated with resource partitioning along dietary and microhabitat lines: it ranged from species that consume liquid foods, engage in group foraging, and mainly nest in the vegetation to species that consume insects and seeds, engage in individual foraging, and demonstrate strictly diurnal activity. Our findings establish a proficient ecological trait‐based animal research that minimizes the number of traits to be measured while maximizing the number of relevant trait dimensions. Overall, resource exploitation in animals might be framed by behavioral dominance, foraging strategy, diet, and nesting habitat; the position of animal species within this trait space could provide relevant information about their distribution and abundance, for today as well as under future global change scenarios.